Conflict and cooperation with trade partners. Issue 2 (4th March 2021) - Peterson, Timothy M.; Zeng, Yuleng
ABSTRACT: Escalating political conflict between major trade partners such as the US and China appears puzzling given theories linking trade to pacific international relations. We reconsider theories on bilateral trade, exposure to the global economy, and politics in order to explain contemporary events. Our approach departs from previous work in three key ways: we examine a broader range of conflictual and cooperative interactions together; we assume leaders are responsive to interests opposed to trade as well as to those who benefit; and we reconceptualize what it means to be a "major trade partner, " presenting a new definition that varies with the dispersion of a state's trade across partners rather than merely dollar value or GDP composition of trade. We demonstrate that states generally initiate more conflict and more cooperation with major trade partners; and while higher exposure to the global economy reduces conflict initiation against major trade partners, it also reduces cooperation. Simultaneously, higher exposure to the global economy is associated with more initiation of cooperation with non-major trade partners. Using events data spanning 1995–2012, we find empirical support for our expectations.